Videography in Migration Research: A Practical Example for the Use of an Innovative Approach - Rebstein, Bernd (Qualitative Sociology Review, 2012)
This article is an example of the practical application of natural video recordings to qualitative research. It describes the videographic method in relation to an ongoing project concerned with forms of knowledge communication within the field of migration. In this field, our visual approach provides a novel perspective on the well-known questions of cross-cultural communication and integration. Firstly, I want to discuss Videography and Genre Analysis in the form of an iterative, audiovisual data collection procedure and define the process of sequence selection and interpretation. Secondly, I will demonstrate how communicative structures are analyzed at different levels of Genre Analysis through the minute analysis of a short audiovisual data sequence from a roadshow that took place during a Latin American theme week. As well as detailing the process of gathering information on a situational level, I want to demonstrate the potential of the analysis to gather information about the structural environment on a transsituational level. Through this discussion, I will also outline the importance of additional contextual information that – by means of further ethnographic research – could be uncovered in our fieldwork.